VD_FINDINFO HC / 2011 / 33 vom 11. Januar 2011 - VD Tribunal cantonal (2011)
PROROGATION DE FOR, COMPÉTENCE, VOLONTÉ RÉELLE, INTERPRÉTATIONSENS GÉNÉRAL, REPRÉSENTATION DIRECTE | 32 al. 1 CO, 452 al. 1ter CPC, 452 al. 2 CPC, 465 al. 1 CPC, 60 CPC, 7 LFors, 9 LFors, 405 al. 1 CPC (CH)